The regularity of the country’s GDP growth rate changes influence on the volume of gross fixed capital formation - Kononenko, Igor; Repin, Anton (Human Geography Journal, 2017)
The regularity of a country’s GDP growth rate changes affecting capital investment volume into its economy for countries with a different economic state was proposed. One of the features of this regularity is as follows: there is an obvious increase of capital investment providing that GDP growth rate exceeds a certain threshold. Moreover, this increase occurs at any changes of the GDP growth rate of the above-threshold region. For the first time, this regularity was discovered in 2005 for the European transition economy countries.  The objective of this work is to test the regularity of GDP’s growth rate change influence on the volume of Gross fixed capital formation for countries with different levels of economic state within the period 1995 – 2013. To achieve the goal, the economic processes taking place in 35 countries around the world were analyzed. The verified result of the analyzed economies demonstrated a high rate of correspondence. On average, in 93.52 % of cases of the economies of the countries analyzed the capital formation was held according to the regularity. In 14 of the 35 countries, investment processes came up to it. Moreover, with the growth of the period considered compared to the previous study, the corresponding percentage rose from 90.7 to 93.52 despite the world crisis.